QUANTIFICATION OF GREEN AND BLUE WATER IN WATERSHEDS ECOSYSTEM: A CASE OF WAMI RUVU BASIN, TANZANIA (The Journal of Building and Land Development, 2022)
The partition of green and blue water, which is driven by hydrological processes, has become a useful aspect in the study of water cycles in basins. While most researches have been conducted on blue water, only a few have been done on the remaining bigger portion representing green water. Wami Ruvu Basin is among the nine-water basins in Tanzania flushing the Middle Eastern part of the country into the Indian Ocean. Currently, there is no published research on green water distribution in Wami Ruvu Basin. This study was conducted to determine the green water potential in the basin using the SWAT model. The study analyzed the variability of green and blue water availability in the Wami Ruvu Basin during the last three decades (1990-2020), based on the water balance equation. The results indicate that the average annual green water resource of the Wami Ruvu Basin was 1037.49mm (about 69%), while the blue water resource constituted 490.96mm (31%) which is comparable to expected values of 60-80%. This signifies the presence of high temperature that leads to high evapotranspiration which limits the amount of water penetrating the soil profile and replenishing the shallow groundwater stored in the wet season.Keywords: green/blue water, water balance, Tanzania.